Determination of canine ROTEM Sigma reference ranges and comparative analysis with ROTEM Delta - Jourdan, Aurélie; Noval Montero, Julia; Troussier, Geoffrey; Anderco, Anna; Dania, Caroline; Moumadah, Yann; Cambournac, Maxime (Frontiers in Veterinary Science, 2026)
IntroductionHemostatic dysfunctions are frequent in critically ill dogs and can markedly affect clinical outcomes. Conventional plasma-based coagulation testing provides limited insight into the complex in vivo interactions among platelets, red blood cells, and coagulation factors. Viscoelastic testing has emerged to overcome these limitations by assessing the dynamics of clot formation and breakdown in whole blood. Among these, ROtational ThromboElastoMetry (ROTEM) provides a real-time evaluation of the coagulation process, reflecting clot initiation, propagation, and lysis. The recently developed ROTEM Sigma analyzer automates reagent handling and measurement minimizing operator variability and pre-analytical errors. Despite its growing use in human medicine, canine reference intervals for the ROTEM Sigma platform have not yet been established.ObjectiveTo determine the reference intervals for ROTEM Sigma parameters in healthy dogs, to compare these values with published ROTEM Delta data, and to assess the influence of physiological variables such as age, sex, body weight, and neuter status.MethodsA prospective observational study was conducted in 42 clinically healthy dogs. Whole blood samples were analyzed using ROTEM Sigma EXTEM, INTEM, FIBTEM, and HEPTEM assays. Reference intervals were generated using both conventional parametric and robust median–MAD statistical methods. Comparisons were made with previously reported canine ROTEM Delta data. Multivariate regression explored associations between ROTEM parameters and demographic or hematologic variables.ResultsReference intervals were successfully defined for all ROTEM Sigma parameters (CT, CFT, A10, MCF, LI60, and G). EXTEM values agreed most closely with previously published ROTEM Delta data, whereas INTEM and FIBTEM exhibited greater variability. Regression analysis identified maximum clot firmness (MCF) as the only parameter significantly affected by biological variables. MCF decreased with higher body weight, increased with platelet count and showed minor sex-related differences.ConclusionThis study establishes canine-specific ROTEM Sigma reference intervals. The close concordance with Delta data more (particularly EXTEM) suggests cross platform consistency while highlighting the necessity of dedicated Sigma-specific reference ranges. Body weight, sex, and platelet count were the primary determinants of MCF. These validated reference intervals enhance the clinical applicability of ROTEM Sigma for assessing hemostatic function in dogs.